Production of hydrogen gas from water via electrolysis for community power generation - Hermharn, Wichien; Kradang-nga, Sittichot; Kachapongkun, Pongsakorn; Jirawongnuson, Sirichai (Institute of Advanced Engineering and Science, 2025)
Rural and remote communities often rely on diesel generators, which are costly, inefficient, and emit greenhouse gas and particulate pollutants. This study combines real-time hydrogen production via electrolytic water separation with a conventional 5,871-cc diesel backup generator to enhance combustion performance and reduce environmental impacts. A self-built electrolyzer was powered by a direct current (DC) battery and precisely controlled by an electronic control unit (ECU) to provide hydrogen output based on engine load conditions. The results of testing co-fueling improved fuel efficiency by 20-25%, with a peak 24.9% reduction in fuel consumption at 50% load. Emission measurements revealed significant reductions in black smoke, PM₂.₅, PM₁₀, and CO₂, with the maximum CO₂ reduction of 23.4 kg CO₂-e/hr. The system operates without the need for a hydrogen storage tank, thus improving safety and reliability. These findings demonstrate that this low-cost and low-emission approach represents a practical alternative for backup power in remote areas. Future work will focus on long-term stability and monitoring hydrogen flow rates for varying load conditions.